New perspective of the bHLH-MYB complex in jasmonate-regulated plant fertility in arabidopsis. (1st February 2016) - Chen, Xi; Huang, Huang; Qi, Tiancong; Liu, Bei; Song, Susheng
ABSTRACT: Jasmonates (JAs) are a class of plant hormones, essential in plant development and defense. JA induces the interaction of the JA receptor Coronatine Insensitive 1 with jasmonate ZIM-domain (JAZ) proteins, and promotes subsequent JAZs degradation, leading to the release of downstream factors and activation of diverse plant development and defense processes. We recently revealed that the IIIe bHLH transcription factors MYC2, MYC3, MYC4 and MYC5 interact with the MYB transcription factors MYB21 and MYB24 to form the bHLH-MYB complex, and JAZs repress the bHLH-MYB complex to regulate JA-mediated stamen development. Here, we further discuss the different properties of the components of the bHLH-MYB complex in expression pattern and stamen regulation.